2016
DOI: 10.12659/msmbr.900242
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Induced Bone Marrow Mesenchymal Stem Cell Chondrogenic Differentiation and its Repair of Articular Cartilage Injury in Rabbits

Abstract: BackgroundWe explored the effect of parathyroid hormone (PTH)-induced bone marrow stem cells (BMSCs) complexed with fibrin glue (FG) in the repair of articular cartilage injury in rabbits.Material/MethodsForty-eight rabbits randomized into four groups were subjected to articular surgery (cartilage loss). The PTH and non-PTH intervention groups included transplantation with PTH/BMSC/FG xenogeneic and BMSC/FG xenogeneic complexes, respectively, into the injured area. The injured group contained no transplant whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…For a-c, data represent mean ± SD, n = 4, *P < 0.05, **P < 0.01, ***P < 0.001, and ****P < 0.0001. For d, data represent mean ± SD, n = 6, a single asterisk is used for all levels of significance when P < 0.05 outcomes [18,[20][21][22][23]. In this study, we used a micropellet platform [24] with the aim of generating more definitive insights into how intermittent or constant PTH treatment influenced BMSC chondrogenesis and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a-c, data represent mean ± SD, n = 4, *P < 0.05, **P < 0.01, ***P < 0.001, and ****P < 0.0001. For d, data represent mean ± SD, n = 6, a single asterisk is used for all levels of significance when P < 0.05 outcomes [18,[20][21][22][23]. In this study, we used a micropellet platform [24] with the aim of generating more definitive insights into how intermittent or constant PTH treatment influenced BMSC chondrogenesis and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…PTH has been explored in BMSC differentiation cultures with varying results. Chen et al reported that PTH-induced rabbit BMSC chondrogenesis resulted in better repair of articular cartilage injury in rabbits, compared with non-PTH-treated BMSC [20]. Zhang et al observed a dose-dependent effect, whereby lower concentrations (1-10 nM) of PTH promoted BMSC chondrogenesis, while higher concentrations (> 100 nM) suppressed matrix production [18].…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroid hormone (PTH) (1-34) inhibits the hypertrophy of BMSCs during chondrogenic differentiation [16,17], inhibits articular cartilage degeneration, and promotes articular chondrocyte proliferation and ECM synthesis [18]. Therefore, it is often used in studies on cartilage tissue engineering as well as in osteoarthritis treatment [19][20][21]. Orth et al [22] reported that injection of PTH (1-34) into a rabbit model of osteochondral defect significantly increased the expression of PTH receptor in chondrocytes and osteocytes in the rabbit joint, improved the surface structure and integration of articular cartilage, and reconstructed the subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
“…microfractures) or procedures in which an overwhelming concentration of MSCs is combined with chondrocytes, for example during a one-stage cartilage repair procedure. Previous work indeed indicated that PTH-induced rat bone marrow-derived MSCs complexed with fibrin glue effectively promoted repair of a rabbit articular cartilage injury [53]. Stem cells are usually derived from fat or bone marrow [54], but also other cell sources have been proposed, such as human dental pulp stem cells [55] or follicle cells enveloping the dental germ [56].…”
Section: Discussionmentioning
confidence: 99%